2006
DOI: 10.1007/s00213-006-0420-5
|View full text |Cite
|
Sign up to set email alerts
|

No effects of enhanced central norepinephrine on finger-sequence learning and attention

Abstract: Selective stimulation of the central noradrenergic system did not promote skilled motor learning or performance as assessed by finger-sequences. The plasticity-enhancing effect of reboxetine, documented in other studies, appears to be dependent on specific neurophysiological and neuropsychological characteristics of the task, and cannot be generalized to other behavioral paradigms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
(42 reference statements)
1
8
0
Order By: Relevance
“…[65] found effects of serotonin on probabilistic learning but did not find any significant changes on the same task after intake of the selective noradrenaline reuptake inhibitor atomoxetine. In addition, reboxetine, another selective noradrenaline reuptake inhibitor, showed no effect on finger sequence learning [80]. In a study that used clonidine, which among other things reduce the noradrenaline turnover, no effect was observed on a procedural motor learning task described below [68].…”
Section: Noradrenalinementioning
confidence: 99%
“…[65] found effects of serotonin on probabilistic learning but did not find any significant changes on the same task after intake of the selective noradrenaline reuptake inhibitor atomoxetine. In addition, reboxetine, another selective noradrenaline reuptake inhibitor, showed no effect on finger sequence learning [80]. In a study that used clonidine, which among other things reduce the noradrenaline turnover, no effect was observed on a procedural motor learning task described below [68].…”
Section: Noradrenalinementioning
confidence: 99%
“…Contrary to expectations, reboxetine (8 mg single dose) did not improve attention, memory or learning in healthy adults [79][80][81]. It has been suggested that a single dose is not sufficient for significant effectiveness on cognitive performances.…”
Section: Selective Norepinephrin Reuptake Inhibitorsmentioning
confidence: 87%
“…Similar effects of NE on M1 excitability could be demonstrated for the NE reuptake inhibitor reboxetine. Plewnia and coworkers [17,19,22] showed enhanced corticospinal and intracortical excitability and improved motor skills in healthy subjects suggesting that this is an effect of NE reuptake inhibitors. This assumption could not be verified by Foster and coworkers [23].…”
Section: Discussionmentioning
confidence: 99%